Exhaled nitric oxide in assessing a group of ice speed skaters - Appodia, M.; Gianfelici, A.; Todaro, A. (Medicina dello Sport, 2016)
AIM: The aim of our research was to verify if the hyperventilation of cold air during physical exercise can be an inflammatory stimulus to the airways, detectable by measuring the fractional exhaled Nitric Oxide (FeNO) and the spirometric data (flow-volume curve). METHODS: We examined 9 elite ice speed skaters (short track). The research was conducted inside the Ice Palace of Courmayer, where the athletes were submitted to a specific training session on the ice rink at an ambient temperature of 6.5 °C. In basal conditions at rest, at the end of the training session and during the subsequent recovery phase the spirometric and FeNO measurements were taken. RESULTS: The data obtained did not reveal inflammatory changes in the airways and/or bronchospasmogenic. And yet, the FeNO showed a particular trend at hyperventilation of cold air during physical exercise with a significant drop in the values detected immediately at the end of the training session. This trend would seem to be more the consequence of the ventilatory level than the effect of the cold air. CONCLUSIONS: Based on the data collected and those of literature the FeNO trend during physical exercise hyperventilating cold air is very particular and requires further studies to understand its meaning and the possible functional consequences.